Pengembangan Video Edukasi Kartun Animasi Berbasis Pendidikan Karakter Pada Materi Hukum II - Andry Fitrian; Yulian Dinihari (Faculty of Teacher Training and Education of Undaris, 2026)
The lack of innovation among teachers in developing instructional media can lead to problems in classroom learning activities. Therefore, this study aims to develop an educational animated cartoon video on the topic of Newton’s Second Law to facilitate learning for tenth-grade senior high school students. The focus of this research is to develop the animated educational video and to determine its effectiveness as alearning medium. This study employs a Research and Development (R&D) method by adopting the ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation). Data were collected using a Likert-scale questionnaire, and the data analysis was conducted through validation by media experts, subject-matter experts, and language experts. The results show that the developed learning media in the form of an animated cartoon video, created using the Kinemaster application on the topic of Newton’s Second Law, obtained an average validation score of 75, which falls into the “good” category. Furthermore, theaverage score for the effectiveness of the animated video in student learning reached 100, which is categorized as “very effective”.Keywords: Educational Videos, Animated Cartoons, Newton’s Second Law.